Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s13756-021-00959-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on healthcare-associated infections in intensive care unit patients: a retrospective cohort study

Abstract: Background During the intensive care units’ (ICUs) reorganization that was forced by the COVID-19 emergency, attention to traditional infection control measures may have been reduced. Nevertheless, evidence on the effect of the COVID-19 pandemic on healthcare-associated infections (HAIs) is still limited and mixed. In this study, we estimated the pandemic impact on HAI incidence and investigated the HAI type occurring in COVID-19 patients. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
62
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 43 publications
11
62
0
4
Order By: Relevance
“…The most common bacteria with multiple genome copies were S. aureus , H. influenzae and Moraxella catarrhalis [ 19 ]. In Italy, the prevalence of HAIs among COVID-19 patients was 56.73% [ 20 ]. However, a study conducted in Germany reported 34% of bacterial co-infections [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common bacteria with multiple genome copies were S. aureus , H. influenzae and Moraxella catarrhalis [ 19 ]. In Italy, the prevalence of HAIs among COVID-19 patients was 56.73% [ 20 ]. However, a study conducted in Germany reported 34% of bacterial co-infections [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were COVID positive patients admitted to the PICU and IMCU; however, our study showed a reduction in HAI in the PICU in contrast to reports from the US and other countries. [32][33][34] Reports from these countries did not indicate the use of continuously-operating adjunct technology for environmental cleaning and disinfection.…”
Section: Discussionmentioning
confidence: 99%
“…Despite improvement of prevention and control strategies, some single-center studies have observed an increase in HA-CDI cases during the COVID-19 pandemic [ 42 , 54 , 55 ] ( Table 1 ). In the study of Sandhu et al, conducted in a hospital of Michigan, USA, the rate of CDI increased from 3.32/10,000 patient-days during January–February 2020 to 3.6/10,000 patient-days during March–April 2020.…”
Section: And the Covid-19 Pandemicmentioning
confidence: 99%
“…Nevertheless, some factors may contribute to the exposure of COVID-19 patients to a higher risk of CDI, as highlighted in a recent study conducted in an Italian hospital, in which, although the total CDI incidence was not significantly changed compared with the pre-pandemic period, a higher CDI incidence was observed in COVID-19 wards compared with that observed in COVID-19 free wards [ 35 ]. In this regard, it is notable that COVID-19 seems to have adversely affected some HAIs and, in particular, increased incidence rates for device-related HAIs have been reported in COVID-19 patients [ 28 , 33 , 55 , 58 , 59 ] ( Table 1 ). The growing burden of HAIs different from CDI, may indirectly favor CDI occurrence due to worsening of the patient's condition, prolongation of hospitalization and possible repeated antibiotics treatments.…”
Section: What About CDI In the Next Future?mentioning
confidence: 99%